THU0625-HPR ELECTRONIC PATIENT-REPORTED OUTCOMES: A SURVEY ABOUT ACCEPTANCE, USAGE AND BARRIERS AMONG GERMAN RHEUMATOLOGISTS. (2nd June 2020) - Krusche, M.; Klemm, P.; Grahammer, M.; Mucke, J.; Vossen, D.; Kleyer, A.; Sewerin, P.; Knitza, J.
Abstract : Background: The use of patient-reported outcomes (PROs) allows for patient-centered, measurable and transparent care. Electronic PROs (ePROs) have many benefits and hold great potential to improve current usage of PROs; yet, limited evidence exists regarding acceptance, usage and barriers among rheumatologists. Objectives: This study aimed to evaluate the current level of acceptance, usage, and barriers among German rheumatologists regarding the utilization of ePROs. The importance of different ePRO features for rheumatologists was investigated. Additionally, the most frequently used PROs for patients with rheumatoid arthritis (RA) were identified Methods: Data was collected via an online survey consisting of 18 questions. The survey was completed by members of the Working Group Young Rheumatologists of the German Society for Rheumatology (Deutsche Gesellschaft für Rheumatologie (DGRh)) at the annual 2019 DGRh conference. Only members currently working in clinical rheumatology were eligible to complete the survey. Results: A total of 119 rheumatologists completed the survey. 90% reported collecting PROs in routine practice and 25.5% already used ePROs. 44.3% were planning to switch to ePROs in the near future.The main reason for collecting PROs was for clinical decision making (66.4%), followed by research (39.5%), reimbursement (23.5%), internal quality management (21.9%) and patient satisfaction (16.8%). The most commonly cited reason for not switching to ePROs was the unawareness of suitable software solutions (figure 1 ).Respondents were asked to rate the features for ePROs on a scale of 0-100 (0 = unimportant, 100 = important). The most important features were automatic score calculation and display (score: 77.5), as well as the simple data transfer to medical reports (76.9) (table 1 ).When asked about PROs in RA, the respondents listed pain, morning stiffness and physician global assessment (PGA) as the most frequently used PROs (figure 2 ). Conclusion: The potential of ePROs is widely seen, and there is a great interest in ePROs. Despite this, a minority of physicians only uses ePROs, and the main reason for not implementing was cited as the unawareness of suitable software solutions. Developers, patients and rheumatologists should work closely together to help realize the full potential of ePROs and ensure a seamless integration into clinical practice. Disclosure of Interests: Martin Krusche Consultant of: Sanofi, Novartis and Medac, Speakers bureau: Roche/Chugai, Novartis, Sobi, , Philipp Klemm Consultant of: Lilly, Medac, Manuel Grahammer Shareholder of: MG is MD and shareholder of Abaton GmbH, Johanna Mucke: None declared, Diana Vossen Consultant of: Medac, Novartis, Abvie, Speakers bureau: Abvie, BMS, Arnd Kleyer Consultant of: Lilly, Gilead, Novartis, Abbvie, Speakers bureau: Novartis, Lilly, Philipp Sewerin Grant/research support from: AbbVie Deutschland GmbH & Co. KG Bristol-Myers Squibb Celgene GmbH Lilly Deutschland GmbH Novartis Pharma GmbH Pfizer Deutschland GmbH Rheumazentrum Rhein-Ruhr, Consultant of: AMGEN GmbH AbbVie Deutschland GmbH & Co. KG Biogen GmbHBristol-Myers Squibb Celgene GmbH Chugai Pharma arketing Ltd. / Chugai Europe GmbHHexal Pharma Janssen-CilagGmbH Johnson & Johnson Deutschland GmbHLilly Deutschland GmbH / Lilly Europe / Lilly Global Novartis Pharma GmbH Pfizer Deutschland GmbH Roche Pharma Rheumazentrum Rhein-Ruhr Sanofi-Genzyme Deutschland GmbH Swedish Orphan Biovitrum GmbH UCB Pharma GmbH, Speakers bureau: AMGEN GmbH AbbVie Deutschland GmbH & Co. KG Biogen GmbHBristol-Myers Squibb Celgene GmbH Chugai Pharma arketing Ltd. / Chugai Europe GmbHHexal Pharma Janssen-CilagGmbH Johnson & Johnson Deutschland GmbHLilly Deutschland GmbH / Lilly Europe / Lilly Global Novartis Pharma GmbH Pfizer Deutschland GmbH Roche Pharma Rheumazentrum Rhein-Ruhr Sanofi-Genzyme Deutschland GmbH Swedish Orphan Biovitrum GmbH UCB Pharma GmbH, Johannes Knitza Grant/research support from: Research Grant: Novartis